Integrating earth observation and other data sources for pastoralist and stakeholder's early action - Alemayehu, Sintayehu (Bioversity International and the International Center for Tropical Agriculture, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025